Draft Annual Plan 1990-91 Union Territory of Dadra and Nagar Haveli - Planning Commission (Planning Commission, 1990)
The Union Territory of Dadra and Nagar Haveli is situated on the western coast of India, nearly 200 Kms. north of Bombay. It is sandwitched between the Valsad District of Gujarat and Thane District of Maharashtra. The coast of Arabian sea is about 30 Kms. and the N.H.8 is running at the distance of about 4 to 5 Kms. from the borders of this Territory. For nearly two centuries after the area was handed over by the Marathas in 1779, it remained a colony of the Portuguese till its liberation in 1954.
Planning Division, Administration Dadra and Nagar Haveli